Queering Mennonite literature: archives, activism, and the search for community - Cruz, Daniel Shank (The Pennsylvania State University Press, 2019)
Introduction : queering Mennonite literature -- Building a queer Mennonite archive -- Searching for selfhood in Jan Guenther Braun's Somewhere else -- Queering tradition in Jessica Penner's Shaken in the water -- Stephen Beachy's boneyard, the Martyrs mirror, and Anabaptist activism -- The queer ethical body in Corey Redekop's Husk -- Trans Mennonite literature -- Epilogue : the future of queer Mennonite literature